Ultrasonic Velocity Studies of Dioxane Solutions of 1,1'-Bis (4-Hydroxyphenyl) Cyclohexane and 4,4'-Dihydroxy Diphenyl Sulfone at 30oC - Baluja, Shipra; Shah, A.R.; Parsania, P.H. (Asian Journal of Chemistry, 2010)
The densities and ultrasonic velocities of 1,1'-bis(4-hydroxyphenyl) cyclohexane and 4,4'-dihydroxy diphenyl sulfone in dioxane solutions (0.04-0.25 M) are studied at 30°C at a frequency of 3 MHz. Various acoustical parameters such as isentropic compressibility (Ks), Rao's sound function (R), Van der Waals constant (b) are evaluated and correlated with concentration. The results are interpreted in terms of solute-solvent interaction.